Ovarian down Regulation by GnRF Vaccination Decreases Reproductive Tract Tumour Size in Female White and Greater One-Horned Rhinoceroses - Hermes, Robert (Public Library of Science, 2016)
Reproductive tract tumours, specifically leiomyoma, are commonly found in female rhinoceroses. Similar to humans, tumour growth in rhinoceroses is thought to be sex hormone dependent. Tumours can form and expand from the onset of ovarian activity at puberty until the cessation of sex-steroid influences at senescence. Extensive tumour growth results in infertility. The aim of this study was to down regulate reproductive function of tumour-diseased and infertile females to stop further tumour growth using a Gonadotropin releasing factor (GnRF) vaccine. Four infertile southern white (Ceratotherium simum simum) and three Greater one-horned rhinoceroses (rhinoceros unicornis) with active ovaries and 2.7 ± 0.9 and 14.0 ± 1.5 reproductive tract tumours respectively were vaccinated against GnRF (Improvac®, Zoetis, Germany) at 0, 4 and 16 weeks and re-boostered every 6–8 months thereafter. After GnRF vaccination ovarian and luteal activity was suppressed in all treated females. Three months after vaccination the size of the ovaries, the number of follicles and the size of the largest follicle were significantly reduced (P<0.03). Reproductive tract tumours decreased significantly in diameter (Greater-one horned rhino: P<0.0001; white rhino: P<0.01), presumably as a result of reduced sex-steroid influence. The calculated tumour volumes were reduced by 50.8 ± 10.9% in Greater one-horned and 48.6 ± 12.9% in white rhinoceroses. In conclusion, GnRF vaccine effectively down regulated reproductive function and decreased the size of reproductive tract tumours in female rhinoceros. Our work is the first to use down regulation of reproductive function as a symptomatic treatment against benign reproductive tumour disease in a wildlife species. Nonetheless, full reversibility and rhinoceros fertility following GnRF vaccination warrants further evaluation.